PENGGUNAAN PERANTI KOHESI DALAM CERPEN SURAT KABAR JAWA POS EDISI BULAN JANUARI—JULI 2016 - Aminudin, Moh Zaki (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2016)
This study aimed to describe the use and appliance faults cohesion in the short story Jawa Pos Newspaper edition in January-April 2016. The appliance cohesion in question, namely (1) grammatical cohesion, which includes reference, substitution, ellipsis, and conjunction (the coupling. (2 ) Then, lexical cohesion which include repetition, synonyms, antonyms, hyponymy and hypernymy, collocation (collocation), and equivalence. this study used a qualitative descriptive method. the data source of this research is the short story of Newspaper jawa Post edition from January to July 2016.The study concluded that the short story Newspaper Tuban jawa Pos in writing short stories in 2016 were able to use a variety of devices cohesion both lexical and grammatical cohesion cohesion. on the other hand they also made mistakes in the use of appliances cohesion.